2018
DOI: 10.3390/antiox7120177
|View full text |Cite
|
Sign up to set email alerts
|

Piecing Together How Peroxiredoxins Maintain Genomic Stability

Abstract: Peroxiredoxins, a highly conserved family of thiol oxidoreductases, play a key role in oxidant detoxification by partnering with the thioredoxin system to protect against oxidative stress. In addition to their peroxidase activity, certain types of peroxiredoxins possess other biochemical activities, including assistance in preventing protein aggregation upon exposure to high levels of oxidants (molecular chaperone activity), and the transduction of redox signals to downstream proteins (redox switch activity). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…In addition, the most enriched ontology in allantois fluid is the peroxidoxin activity. Peroxidoxin in an antioxidant enzyme related to genome stability (West et al, 2018). Then, we can hypothesize that the high metabolic allantois epithelium could produce peroxidoxin to inhibit possible oxidants eliminated in the allantois fluid by fetal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the most enriched ontology in allantois fluid is the peroxidoxin activity. Peroxidoxin in an antioxidant enzyme related to genome stability (West et al, 2018). Then, we can hypothesize that the high metabolic allantois epithelium could produce peroxidoxin to inhibit possible oxidants eliminated in the allantois fluid by fetal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in line with earlier results for Saccharomyces cerevisiae which demonstrated that the yeast was still viable despite a deletion of all five peroxiredoxin genes and that single mutants grew like the wild type in aerobic conditions [ 36 ]. Interestingly, the authors also showed that the Asp f3 orthologue in yeast, Tsa1p, secured long-term genomic stability by preventing mutations [ 37 , 38 ]. Such a protective function may well be conserved in A. fumigatus but would most likely not explain the avirulent phenotype of the Δ asp f3 strain in the aspergillosis animal model.…”
Section: Discussionmentioning
confidence: 99%
“…A peroxidatic cysteine reduces the peroxide to water. Thioredoxin system reduce peroxiredoxins restoring to them their catalytically active form (West et al, 2018).…”
Section: Protein Descriptionmentioning
confidence: 99%